Exploring self‐blame and the perceived causes of preeclampsia in urban Ghana. Issue 2 (11th September 2020) - Joshi, Avina; Beyuo, Titus; Oppong, Samuel A.; Owusu, Andrews; Moyer, Cheryl A.; Lawrence, Emma
Abstract : Many women blame themselves for the development of preeclampsia, and patients may benefit from an explicit discussion about the causes of preeclampsia with their healthcare provider.